Inter-semiotic cohesion analysis of multimodal elements in Iranian English textbooks / Masoumeh Mahdizadegan Attar - Attar, Masoumeh Mahdizadegan (2014)
This study attempts to firstly explore the verbal and visual representations and secondly to investigate textual cohesive devices between the two different semiotic resources, language and image, in Iranian English textbooks for the Middle school students. To fulfil the aim of this study, three analytical frameworks were adopted to examine the texts. Using Halliday’s (1994, 2004) Transitivity System, verbal texts of the data were analysed in order to find out the experiential meaning of the linguistic texts. In the next stage, Kress and van Leeuwen’s (1996, 2006) model of Representation Analysis was applied to identify the experiential meaning of the visual imageries in the texts. Finally, textual cohesion of the texts was analysed based on Liu and O’Halloran’s (2009) Textual Cohesive Devices. The corpus of the study consists of 24 dialogue sections of all three Iranian English Textbooks which are provided for Middle school students who begin learning English language at this level. The analysis of the dialogue sections reveals that the sequence of the processes identified in the three textbooks mirror the level of language proficiency to be acquired across the textbooks. Concrete and tangible clauses such as Relational and Material are presented in the first textbook to interact with beginners in learning the English language. Mental process that expresses the inner feelings and deals with more abstract matters and is not about concreteness like the Material process is exclusively found in the third textbook, the book used with the more proficient students of the English language as they would already have undergone two years of learning the language. The visual narrative analysis of the data discovers that Action process is the most frequently found process in all the dialogues of the three English textbooks. This is justifiable as Action process illustrates what is going on and what is happening in the speakers’ stories or in whatever the speakers are doing while speaking. This contributes towards the English learners’ understanding of what is expressed in the verbal texts of the dialogues. The verbal texts of the dialogues are very short and their clauses are obviously simple; therefore, visual imageries take the role of complementing the verbal texts to provide the details though through the visual form. This study would like to introduce what it labels as communication process whereby this process is realized by two processes that exist simultaneously. This is unlike previous processes proposed in Kress and van Leeuwen’s (2006) framework. The textual cohesion analysis of the dialogues shows that images and verbal texts are not strongly cohesive. Primarily, all images of the dialogues are only drawings with low colour contrast that remove the reality of the images. Therefore, although the images are identified as providing the details of the dialogues, they could not clearly illustrate the details. This fact somewhat erodes the cohesion between image and the verbal text especially when analysing cohesion in terms of referencing is concerned. Furthermore, most of the images consist of two main participants who are speakers of the dialogues and the topic of their talk is found not saliently illustrated in the image. This shows that the visual structure and the verbal structure are not in complete parallelism. Finally, the analysis reveals that all images and verbal texts are strongly disconnected through solid framing or space between the two modes, and this further decreases cohesion between image and language in the textbooks. In conclusion, this study hopes to provide valuable information for textbook designers and Iranian teachers using the textbooks and to contribute towards research in the field of multimodality.